Ecocritical Perspectives on Climate Anxiety and Environmental Justice in Contemporary English Fiction - Dr. Banpreet Kour (PT. Radja Intercontinental Publishing, 2025)
This paper investigates how contemporary English-language fiction represents the psychological experience of climate anxiety and the political demands of environmental justice, and how these two concerns, though frequently discussed together, pull literary form in somewhat different directions. Drawing on the ecocritical tradition established by critics such as Lawrence Buell and expanded by Rob Nixon's account of slow violence, the paper argues that climate fiction faces a distinctive representational problem: the causes and consequences of environmental catastrophe are typically dispersed across decades, continents, and social classes in ways that resist the tight, character-centered causality on which the realist novel has traditionally relied. The paper examines the narrative strategies contemporary novelists have developed to address this problem, from multigenerational and multi-species narration to speculative and near-future settings, and considers how environmental justice fiction in particular insists on connecting ecological harm to preexisting patterns of racial and economic inequality. The paper concludes that the most successful climate fiction does not simply add environmental content to existing novelistic form, but reworks the novel's traditional assumptions about scale, agency, and time.